Sikap dan Pencapaian Pelajar-Pelajar Geografi - Kolendai, Govindasamy (1998)
The purpose of this study is to explore the correlation between student’s attitude towards geography and their achievement in this subject. It further explores the factors contributing to their attitudes such as teachers role, peer group influence, the parental support and the socio-economical status. Particularly this study attempts to explain whether (1) there is any significant correlation between student’s attitude towards geography and their achievement in this subject; (2) there is any significant correlation between student’s attitude towards geography and the factors of teacher’s role, peer group influence and the parental support; (3) there is any significant difference in the attitude of the geography students between gender; between urban and rural school students; between races; between the levels of parent’s occupations; between the levels of parent’s education; and between the levels of parent’s income; (4) the factors of teachers role, peer group influence and the parental support significantly explain the varience in the student’s attitude towards geography. A total of 317 fourth form geography students responded to the survey conducted by questionaire method. Frequencies and percentages were obtained and presented in the form of cross-tabulation and charts. Correlation tests, t-tests, ANOVA and Stepwise multiple regression were used to test the significance between the variables. The results of the study reveals that (1) there is no significant correllation between students attitude towards geography and their achievement in this subject; (2) there is a significant correlation between student’s attitude towards geography and the factors of teacher's role and parental support but not the peer group influence; (3) there is a significant difference in the attitude of geography students between gender; between urban and rural school students; between races; between the levels of parent’s occupation; between the parents income; between those who attend geography tuition classes and not; between those who buy geography revision books and not but there is no significant difference between the levels of parent’s education; (4) the factors of teacher’s role, peer group influence and parental support significantly explain the varience in the attitude of fourth form students towards geography.